Plan de negocios para el taller artesanal de la familia Morales, ubicado en la comunidad de la Compañía, cantón Otavalo, provincia de Imbabura, Ecuador. - Morales Males, Huaita Sisa (2015)
Imbabura is a permanent tourist destination. This province contains a large diversity of landscapes and cultures. Andean landscapes dominated by the Taita Imbabura and Mama Cotacachi and twenty lakes whose environments cities and communities, which still retain their rites and traditions are based. Otavalo is internationally recognized for its market and its natural attractions, becoming a destination for combining cultural tour packages. The publicity generated by: partition as "activity test" for the contestants of international reallity called The Amazing Race Ecuador, monthly visits from groups of foreign students with Vision Found and advertising by word of mouth from some guides who frequent the workshop generated in domestic and foreign tourists, a growing interest in understanding the processes of production of the famous Otavalo crafts. The textile craft workshop Males Morales family, is located in the Compañía community, is a family business that produces belts, ribbons and bracelets made from natural fiber and synthetic yarns, using the spanish loom, artifact used in the mills colonial and callua, tool pre - colonial used to compile ponchos, anacos and blankets. Given the favorable situation of a potential market a business plan for the textile craft workshop is proposed, it will allow effectively utilize the material resources and human talent available, creating an alternative income to the owner family and provide a service visiting domestic and foreign tourists who appreciate the craft. Unlike the competition, this craft workshop will provide a dynamic exhibition; it will allow visitors to learn the entire process of making handicrafts. The business plan helped establish marketing strategies to capture the unmet demand (tourists), the organization of human talent, distribution facilities technically leveraging existing resources in the craft workshop.